New groups of antimycobacterial agents: 6-chloro-3-phenyl-4-thioxo-2H-1,3-benzoxazine-2(3H)-ones and 6-chloro-3-phenyl-2H-1,3-benzoxazine-2,4(3H)-dithiones - Waisser, K; Gregor, J; Kubicová, L; Klimesová, V; Kunes, J; Machácek, M; Kaustová, J (European journal of medicinal chemistry, 2000)
A series of 6-chloro-3-phenyl-4-thioxo-2H-1,3-benzoxazine-2(3H)-ones 3 and a series of 6-chloro-3-phenyl-2H-1,3-benzoxazine-2, 4(3H)-dithiones 4 were synthesized by melting 6-chloro-3-phenyl-2H-1, 3-benzoxazine-2,4(3H)-dione and its derivatives substituted on the phenyl ring 2 with tetraphosphorus decasulfide. Compounds 2c-e, 3 and 4 exhibited in vitro activity against Mycobacterium tuberculosis, M. kansasii (two strains) and M. avium better than or comparable to that of isoniazid. Replacement of the oxo group by a thioxo group at position 4 led to improvement in activity against M. tuberculosis and M. kansasii. The Free-Wilson method and procedure developed by the authors were used to analyse the structure-activity and structure-antimycobacterial profile relationships, respectively.
Keywords: oxaziny; Species Specificity; druhová specificita; Anti-Bacterial Agents; mikrobiální testy citlivosti; Microbial Sensitivity Tests; Mycobacterium; antibakteriální látky; Oxazines